2023
DOI: 10.3847/2041-8213/accd6f
|View full text |Cite
|
Sign up to set email alerts
|

A SPectroscopic Survey of Biased Halos in the Reionization Era (ASPIRE): JWST Reveals a Filamentary Structure around a z = 6.61 Quasar

Abstract: We present the first results from the JWST program A SPectroscopic survey of biased halos In the Reionization Era (ASPIRE). This program represents an imaging and spectroscopic survey of 25 reionization-era quasars and their environments by utilizing the unprecedented capabilities of NIRCam Wide Field Slitless Spectroscopy (WFSS) mode. ASPIRE will deliver the largest ( ∼ 280 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…On the other hand, Farina et al (2017) found one faint LAE companion within the arcminute field of view of MUSE, separated by 12 kpc (2″) and assumed to be undergoing a merger with the quasar host galaxy; this companion is detected with S/N = 2 in H 160 in these data, thus it was not included in our LBG list. Similarly, the overdensity reported by Wang et al (2023) shows an enhancement of bright [O III] emitters with f [O III] >5.0 × 10 −18 erg s −1 cm −2 within 10″ from the quasar, which had faint but visible counterparts in the HST data that did not meet our H 160 detection criteria. In a Subaru Suprime-Cam survey in the J0305 field, Ota et al (2018) also noted a dearth of faint LAEs and LBGs given their 50% completeness limit of m = 26.…”
Section: Evaluating the Significance Of The J0305 Overdensitysupporting
confidence: 81%
See 4 more Smart Citations
“…On the other hand, Farina et al (2017) found one faint LAE companion within the arcminute field of view of MUSE, separated by 12 kpc (2″) and assumed to be undergoing a merger with the quasar host galaxy; this companion is detected with S/N = 2 in H 160 in these data, thus it was not included in our LBG list. Similarly, the overdensity reported by Wang et al (2023) shows an enhancement of bright [O III] emitters with f [O III] >5.0 × 10 −18 erg s −1 cm −2 within 10″ from the quasar, which had faint but visible counterparts in the HST data that did not meet our H 160 detection criteria. In a Subaru Suprime-Cam survey in the J0305 field, Ota et al (2018) also noted a dearth of faint LAEs and LBGs given their 50% completeness limit of m = 26.…”
Section: Evaluating the Significance Of The J0305 Overdensitysupporting
confidence: 81%
“…J0305-3150, at z = 6.6, hosts the strongest overdensity in the sample with 42 LBGs, corresponding to δ gal = 8.8 ± 1.8. In a companion paper, Wang et al (2023) show a spectroscopically confirmed overdensity of [O III] emitters, 13 of which correspond to LBGs reported in this paper. Its coordinated parallel field shows a significant 3σ overdensity, which could be consistent with being part of the same structure.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations